The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1155/2014/851796
|View full text |Cite
|
Sign up to set email alerts
|

Musical Rhythms Affect Heart Rate Variability: Algorithm and Models

Abstract: There were a lot of psychological music experiments and models but there were few psychological rhythm experiments and models. There were a lot of physiological music experiments but there were few physiological music models. There were few physiological rhythm experiments but there was no physiological rhythm model. We proposed a physiological rhythm model to fill this gap. Twenty-two participants, 4 drum loops as stimuli, and electrocardiogram (ECG) were employed in this work. We designed an algorithm to map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 105 publications
0
5
0
1
Order By: Relevance
“…Besides analyzing the nature of ECG signal, many scientists have tried to analyze the influence of different kinds of external stimulation on heart activity. The works reported on analyzing the influence of auditory123, visual456 and olfactory stimuli789 are noteworthy to mention.…”
mentioning
confidence: 99%
“…Besides analyzing the nature of ECG signal, many scientists have tried to analyze the influence of different kinds of external stimulation on heart activity. The works reported on analyzing the influence of auditory123, visual456 and olfactory stimuli789 are noteworthy to mention.…”
mentioning
confidence: 99%
“…We also examined cross-cultural popularity by analyzing song arousal. Following research by [22,37] that found popular music comprised high intensity and strong rhythms, we show that intensity arousal appears to be more cross-culturally popular, but rhythmic arousal appeared inversely related to popularity. This suggests a conceptual differentiation between both arousal domains, and more research is needed to identify the distinct functions and qualities of both.…”
Section: Discussionmentioning
confidence: 52%
“…Energy, in particular, has been shown to reflect the use of cathartic emotional downregulation of anger experiences [20]. Given that past research has found links between music popularity and arousal features (e.g., [21,22], we also examined eigencentrality in the context of musical arousal.…”
Section: Arousal Features In Musicmentioning
confidence: 99%
“…Generally, humans prefer harmonic sounds over dissonance, which has the capacity to distress an individual (McDermott, 2012). In music, the composition of fundamental frequency and harmonics can modulate physiological reactions (synchronization of heart rate to the beat rate of the music) and even emotional states (Det & Fakultet, 2017;Khalfa, Isabelle, Jean-Pierre, & Manon, 2002;Paquette, Peretz, & Belin, 2013;Wang & Huang, 2014). As a consequence, music can have an intrinsic capacity to calm or excite an individual.…”
Section: Part 5: Auditory Perception and Related Cognitive Processesmentioning
confidence: 99%